In vitro evaluation of surface roughness of 4 resin composites after the toothbrushing process and methods to recover superficial smoothness. - dos Santos, Paulo Henrique; Pavan, Sabrina; Consani, Simonides; Sobrinho, Lourenco Correr; Sinhoreti, Mario Alexandre Coelho; Filho, Joao Neudenir Arioli (My University, 2007)
OBJECTIVE: This study evaluated the efficiency of repolishing, sealing with surface sealant, and the joining of both in decreasing the surface roughness of resin-based composites after a toothbrushing process. METHOD AND MATERIALS: Ten specimens of each composite (Alert, Z100, Definite, and Prodigy Condensable), measuring 2 mm in thickness and 4 mm in diameter, were made and submitted to finishing and polishing processes on both sides of the specimens using the Sof-Lex system. The specimens were then subjected to toothbrushing (30,000 cycles), and surface roughness (Ra) was analyzed with a Surfcorder SE 1700 profilometer. The upper surface of each composite was etched with 37% phosphoric acid, and the surface-penetrating sealant Protect-it was applied on 1 surface. The roughness of these surfaces was again measured. On the other side, the surface of the specimen was repolished, and the efficiency of this procedure was measured using the profilometer. The surface roughness resulting from the joining of the 2 methods was verified by applying, in the final stage, the surface-penetrating sealant on the repolished surface. Data were analyzed with analysis of variance and Tukey test (P <.05). RESULTS: Results showed that the lowest surface roughness values were obtained for Definite, Z100, and Prodigy Condensable after the repolishing process and after the repolishing plus sealing. For Alert, the joining of repolishing plus sealing promoted the lowest values of surface roughness. CONCLUSION: Of the resin-based composites, Alert demonstrated the highest values of surface roughness in all the techniques tested.
Keywords: acrylic acid resin; Composite Dental Resin; polyurethan; resin; unclassified drug; analysis of variance; chemistry; methodology; surface property; tooth brushing; Acrylic Resins; Analysis of Variance; Composite Resins; Dental Polishing; Polyurethanes; Surface Properties; Toothbrushing